Simulation case study of deformations and landslides using real-time GNSS precise point positioning technique. Issue 6 (1st November 2016) - Capilla, Raquel M.; Berné, José Luis; Martín, Angel; Rodrigo, Raul
ABSTRACT: The precise point positioning (PPP) is a Global Navigation Satellite System (GNSS) computation technique that performs precise positioning using a single receiver. This is the main advantage over the traditional differential positioning for geodesy and geomatics which requires, at least, two receivers to get a precise position or a single receiver connected to a network of reference stations. The main goal of this work was to study the real-time PPP technique for deformation and landslides monitoring. A custom designed device was used for the simulation of landslides, and several test campaigns were performed at field. A control unit was designed based on open-source software and Python libraries implemented in this research. The conclusion of the study shows that real-time PPP allows solutions for deformation monitoring with mean offsets of 2 cm in north, east and up components, and standard deviations of 2 cm. It demonstrates the reliability of real-time PPP monitoring systems to detect deformations up to 5 cm of magnitude when the double constellation (GPS+GLONASS) was used. Finally, an improvement in the results with the recovery of fixed ambiguities in the PPP algorithms is outlined.